A Lamus-Based Flight Data Sharing Model on Consortium Blockchain. (9th May 2022) - Li, Fengyin; Cui, Yang; Huang, Baogui; Yu, Siqi; Liu, Peiyu; Wang, Yilei; Li, Tao
Abstract : Currently, traditional flight data sharing models cannot resist quantum attacks, which poses the risk of data leakage. The research on the flight data sharing model against quantum attack has become one of the research hotspots. Lattice-based cryptography is recognized as an effective way to resist quantum attacks. A flight data sharing model on consortium blockchain is proposed in this paper to resolve data leakage during data sharing. First, a new lattice-based multisignature scheme (Lamus) is proposed, capable of resisting quantum attacks. We prove the security of the proposed Lamus scheme in the random oracle model. Moreover, a flight data sharing model on consortium blockchain is proposed by applying the proposed Lamus scheme to resist quantum attacks. Security and performance analysis show that the model guarantees antiquantum security, and it achieves good performance in terms of storage efficiency and operating efficiency.